1978
DOI: 10.1002/cjce.5450560601
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent two phase flow in horizontal pipes: Predictive models

Abstract: A semi‐mechanistic model for two phase gas‐liquid slug flow proposed recently by Dukler and Hubbard has been modified and extended to apply to the entire intermittent flow regime. Flow predictions of the model proposed in this paper are compared with detailed experimental data recently obtained for an air‐oil system. The model requires the use of empirical correlations for the slug velocity and the in situ liquid volume fraction in the slug. In addition, either the slug frequencies or length corresponding to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0
7

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(96 citation statements)
references
References 3 publications
3
86
0
7
Order By: Relevance
“…Kouba The observed non-zero intercept of the line with the y-axis shows that there is a drift velocity component of bubbles. This observation supports the conclusions of [4] and [7][8] that a drift velocity exists for the horizontal case and that it may even exceed its value in the vertical case.…”
Section: Determination Of Characterization Parameterssupporting
confidence: 90%
See 3 more Smart Citations
“…Kouba The observed non-zero intercept of the line with the y-axis shows that there is a drift velocity component of bubbles. This observation supports the conclusions of [4] and [7][8] that a drift velocity exists for the horizontal case and that it may even exceed its value in the vertical case.…”
Section: Determination Of Characterization Parameterssupporting
confidence: 90%
“…In contrast, other investigators [4] and [16][17], observed significant drift velocities in horizontal pipes. Weber [7] considered a force balance on the nose of a stationary bubble to explain the absence of drift velocities in horizontal pipes.…”
Section: Slug Velocitymentioning
confidence: 69%
See 2 more Smart Citations
“…Certain authors noted that the average length of the slugs varies little according to the velocity of mixture for air-water flow in horizontal pipeline. As an example, Dukler and Hubbard [22] then Andreussi and Bendiksen [23] observed that varies from 12 to 24d, of 12 until 30d for Nicholson et al [24], Nydal et al [25] finds that varies from 15 until 20d, it is 13,63d until 29,31d for Salhi [19]. In our case, the average length of a slug varies between 12,77d and 33,24d, thus our results are slightly higher than those of Nicholson et al [24] and Salhi [19].…”
Section: Slug Lengthmentioning
confidence: 96%